The murder book - Billingham, Mark (The DI Tom Thorne series, 2022)
"Tom Thorne finally has it all. In Nicola Tanner and Phil Hendricks, Thorne has good friends by his side. His love life is newly reformed by a promising relationship and he is happy in the job he has devoted his life to. As he sets off hunting the woman responsible for a series of grisly murders, Thorne has no way of knowing that he will be plunged into a nightmare from which he may never wake. A nightmare that has a name. Thorne's past threatens to catch up with him and a ruinous secret is about to be revealed. If he wants to save himself and his friends, he will have to do the unthinkable. Tom Thorne finally has a lot to lose"--